2018
DOI: 10.7717/peerj.4293
|View full text |Cite
|
Sign up to set email alerts
|

Are pumas subordinate carnivores, and does it matter?

Abstract: BackgroundInterspecific competition affects species fitness, community assemblages and structure, and the geographic distributions of species. Established dominance hierarchies among species mitigate the need for fighting and contribute to the realized niche for subordinate species. This is especially important for apex predators, many of which simultaneous contend with the costs of competition with more dominant species and the costs associated with human hunting and lethal management.MethodsPumas are a wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 93 publications
2
65
0
Order By: Relevance
“…Disruption of spatiotemporal niche partitioning is likely to be a common outcome of human disturbance, and could increase the frequency at which negative interactions take place among carnivores, thus increasing the potential for interference competition. Such increase in competition can have a negative impact on subordinate carnivores, further reducing the probability of survival of threatened carnivore species (Elbroch & Kusler, 2018). Similarly, the narrowing of the available trophic niche, and associated weakening of trophic partitioning, can increase exploitation competition among carnivore species (Karanth & Sunquist, 1995; Creel et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Disruption of spatiotemporal niche partitioning is likely to be a common outcome of human disturbance, and could increase the frequency at which negative interactions take place among carnivores, thus increasing the potential for interference competition. Such increase in competition can have a negative impact on subordinate carnivores, further reducing the probability of survival of threatened carnivore species (Elbroch & Kusler, 2018). Similarly, the narrowing of the available trophic niche, and associated weakening of trophic partitioning, can increase exploitation competition among carnivore species (Karanth & Sunquist, 1995; Creel et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Red foxes are subordinate to numerous carnivores, including coyotes, wolves, bears, and mountain lions. In North America, research has shown that red fox abundance and behavior are generally limited by coyotes, which in turn are limited by wolves ( Levi & Wilmers, 2012 ; Newsome & Ripple, 2015 ) and potentially mountain lions ( Elbroch & Kusler, 2018 ). Future research needs to determine whether mountain lions act as shields that protect foxes from coyotes, and provide foxes access to resources that otherwise might be secured by coyotes and other dominant scavengers; mountain lion presence may allow foxes to coexist at higher densities with coyotes than in their absence.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in habitat selection between the two continents may reflect competition with distinct sets of carnivoran species. Today, jaguars outcompete mountain lions in moist forest biomes of South America 30 , while wolves outcompete mountain lions in North American grasslands 31 . Furthermore, present differences in habitat selection probably reflect a long history of competition with a much more diverse carnivore guild on both continents during the Pleistocene.…”
Section: Discussionmentioning
confidence: 99%